Examining risk factors for self-harm and suicide in LGBTQ+ young people: a systematic review protocol. Issue 11 (11th November 2019) - Williams, A Jess; Arcelus, Jon; Townsend, Ellen; Michail, Maria
Abstract : Introduction: Young people who identify as Lesbian, Gay, Bisexual, Transgender, Queer or Questioning (LGBTQ+) are at increased risk for self-harm, suicide ideation and behaviours. However, there has yet to be a comprehensive understanding of what risk factors influence these behaviours within LGBTQ+ young people as a whole. The purpose of this systematic review is to examine risk factors associated with self-harm, suicidal ideation and behaviour in LGBTQ+) young people. Methods and analysis: A systematic review will be conducted, conforming to the reporting guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement recommendations. Electronic databases (MEDLINE, Scopus, EMBASE, PsycINFO and Web of Science) will be systematically searched for cross-sectional, prospective, longitudinal, cohort and case–control designs which examine risk factors for self-harm and/or suicidal ideation and behaviour in LGBTQ+ young people (aged 12–25 years). Only studies published in English will be included. No date restrictions will be applied. Study quality assessment will be conducted using the original and modified Newcastle-Ottawa Scales. Meta-analysis or narrative synthesis will be used, dependent on findings. Ethics and dissemination: This is a systematic review of published literature and thereby ethical approval was not sought. The review will be submitted to a peer-reviewed journal, be publicly disseminated at conferences focusing on mental health, self-harm and suicide prevention. The findings will also be shared through public engagement and involvement, particularly those related to young LGBTQ+ individuals. PROSPERO registration number: CRD42019130037.